Zur Realisierung der standardsprachlichen vokalischen Lautwechselprozesse des Frühneuhochdeutschen im Text der Einträge im Rößeler Pfarrbuch aus dem 15. Jahrhundert (bis 1468) = O realizacji standardowych procesów zmiany dźwiękowej w obrębie wokalizmu języka wczesno-nowo-wysoko-niemieckiego w tekście adnotacji reszelskiej księgi parafialnej z XV wieku (do 1468 roku) = On the realization of the standard language vowel sound changes of the early new high German in the text of the entries in the 15th-century parish register from Reszel (until 1468) - Owsiński, Piotr A. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of the phonemic-graphemic analysis of the entries from 15th century, which come from the parish register of city Reszel and were written down in the Silesian dialect of the Early New High German. Due to the analysis it could be proved, the text contains the standard Early New High German features as well as the dialectal structures and the sound changes, which are typical for the Silesian dialect. All the results of the exploration are supported with the appropriate examples.
Keywords: fonem; grafem; język wczesno-nowo-wysoko-niemiecki; dialekt; phoneme; grapheme; sound change; Early New High German; dialect